Upaya Meningkatkan Hasil Belajar Siswa Materi Huruf Hijaiyah dan Harakat Menggunakan Media Plastisin - Faizah; Fitriah, Siti Nur (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2021)
The low results of students' scores on PAI material of hijaiyah letters theme and their harat are the main problems in this research. The reason is, students 'sociological background, students' thinking ability, less creative and innovative teachersin using learning media. This study aims to improve learning outcomes of